Making sense of discourses of sameness and difference in agency responses to abusive LGB and/or T partners. (September 2019) - Donovan, Catherine; Barnes, Rebecca
The success of recent same-sex marriage campaigns worldwide arguably reflects a shift towards recognising parity between lesbian, gay, bisexual and/or trans (LGB and/or T) and heterosexual relationships, whereby LGB and/or T women and men are credited with the same needs and rights regarding intimacy and family life. This contrasts starkly with previous, and to some extent, continuing, discourses of difference, which either celebrate LGB and/or T distinctiveness, or conversely emphasise difference to preserve heterosexual privilege. This article explores how discourses of sameness and difference are reflected in interview data gathered from 23 practitioners who provide perpetrator interventions primarily for domestically violent and abusive heterosexual men. When reflecting on the suitability of these interventions for abusive LGB and/or T intimate partners, discourses of sameness dominated practitioners' assumptions about the needs of LGB and/or T perpetrators. Our conclusions problematise this emphasis on sameness and argue that the development of interventions for abusive LGB and/or T intimate partners needs to be informed by more nuanced understandings of both difference and sameness within and across LGB and/or T and heterosexual people's intimate relationships.